Radiotherapy for early mediastinal Hodgkin Lymphoma according to the German Hodgkin Study Group (GHSG): the roles of intensity-modulated radiotherapy and involved-node radiotherapy - Köck, Julia; Abo-Madyan, Yasser; Lohr, Frank; Stieler, Florian; Wenz, Frederik (International journal of radiation oncology, biology, physics, 2012)
Purpose Cure rates of early Hodgkin lymphoma (HL) are high, and avoidance of late complications and second malignancies have become increasingly important. This comparative treatment planning study analyzes to what extent target volume reduction to involved-node (IN) and intensity-modulated (IM) radiotherapy (RT), compared with involved-field (IF) and three-dimensional (3D) RT, can reduce doses to organs at risk (OAR).Methods and Materials Based on 20 computed tomography (CT) datasets of patients with early unfavorable mediastinal HL, we created treatment plans for 3D-RT and IMRT for both the IF and IN according to the guidelines of the German Hodgkin Study Group (GHSG). As OAR, we defined heart, lung, breasts, and spinal cord. Dose-volume histograms (DVHs) were evaluated for planning target volumes (PTVs) and OAR.Results Average IF-PTV and IN-PTV were 1705 cm3 and 1015 cm3, respectively. Mean doses to the PTVs were almost identical for all plans. For IF-PTV/IN-PTV, conformity was better with IMRT and homogeneity was better with 3D-RT. Mean doses to the heart (17.94/9.19 Gy for 3D-RT and 13.76/7.42 Gy for IMRT) and spinal cord (23.93/13.78 Gy for 3D-RT and 19.16/11.55 Gy for IMRT) were reduced by IMRT, whereas mean doses to lung (10.62/8.57 Gy for 3D-RT and 12.77/9.64 Gy for IMRT) and breasts (left 4.37/3.42 Gy for 3D-RT and 6.04/4.59 Gy for IMRT, and right 2.30/1.63 Gy for 3D-RT and 5.37/3.53 Gy for IMRT) were increased. Volume exposed to high doses was smaller for IMRT, whereas volume exposed to low doses was smaller for 3D-RT. Pronounced benefits of IMRT were observed for patients with lymph nodes anterior to the heart. IN-RT achieved substantially better values than IF-RT for almost all OAR parameters, i.e., dose reduction of 20% to 50%, regardless of radiation technique.Conclusions Reduction of target volume to IN most effectively improves OAR sparing, but is still considered investigational. For the time being, IMRT should be considered for large PTVs especially when the anterior mediastinum is involved.